The Role of Law in Encouraging Innovation in Village Financial Management - Ratna Sari Dewi; Asmuni; Muhammad Yafiz (Faculty of Law, Universitas Pekalongan, 2024)
The purpose of this research is to identify and analyze the role of law in encouraging innovation in village financial management. Through a qualitative approach, this study collected data through interviews, observations, and documentation studies involving various stakeholders, including village officials, communities, and law enforcement. This method allows researchers to understand in depth the dynamics that occur in village financial management as well as the challenges and opportunities faced. The results of the study show that clear and firm regulations are a key factor in encouraging innovation. The law provides a framework that facilitates transparency and accountability in the management of village funds. In addition, regulations requiring community participation in the planning and supervision process further strengthen the relationship between village officials and the community, creating a greater sense of ownership over financial management. This study also found that the application of information technology in village financial management has resulted in increased efficiency and accuracy. The design of information systems that are transparent and easily accessible to the public contributes to better supervision. In addition, training and capacity building of village officials are critical in ensuring they have the necessary skills to manage finances effectively. This research confirms that the law not only functions as a regulatory tool, but also as a driver of innovation in village financial management. By strengthening cooperation between the government, communities, and law enforcement, villages can better manage their resources, thereby improving the overall well-being of the community.